March upcountry - Weber, David, 1952- (Baen ; Distributed by Simon & Schuster, 2002)
When his spaceship crashes en route to a ceremonial appearance on another boring planet, Roger MacClintock, a spoiled young prince, and his guardian Royal Marines must make a perilous trek across a planet whose jungles are filled with carnivorous plants, deadly predators, and enemy barbarians to seek safety.